Penerapan SAK ETAP sebagai Strategi Peningkatan Transparansi Laporan Keuangan: The Implementation of SAK ETAP as a Strategy to Enhance Financial Report Transparency - Hariza, Reisy; Rahmadi, Rahmadi; Fahrudin, Tora (Al Dzahab, 2025)
Purpose: This study aims to analyze the level of compliance in financial statement preparation, identify obstacles in the implementation of SAK ETAP, and conduct an evaluation to assess the quality of financial reporting. Design/Methodology/Approach: A qualitative method with a descriptive approach was employed. Data were collected through interviews, documentation, and literature review. Primary data were obtained directly from informants, while secondary data came from relevant literature and the financial statements of PT. Restu Ibu Rama. The research focuses on evaluating the company’s compliance with SAK ETAP standards. Findings: The implementation of SAK ETAP in the preparation of PT. Restu Ibu Rama’s financial statements has not been fully optimized, as several components and accounts are not properly presented. The main challenges identified include limited understanding of SAK ETAP by the finance team, insufficient human resources, weaknesses in the accounting information system, and inadequate internal control. Research Implications: Strengthening the knowledge and capacity of financial staff, improving the accounting information system, and enhancing internal supervision are necessary steps to ensure that financial statements are more accurate, reliable, and useful as a basis for decision-making. Keywords: SAK ETAP; Financial Statements; Decision Usefulness Theory